Understanding Of Sexual Harassment At The Workplace - Mohd Karim, Anis Farahwahida; Endut, Noraida (2016)
Sexual harassment is the violation of a person’s personal integrity and wellbeing and is an incident that often occurs in a workplace context. While it was mainly associated with situations in a traditional employment workplace, it has also been reported in organizations that consist of non-traditional or mixed employment relationships such as educational institutions. Sexual harassment in a university setting worldwide is quite pervasive. In 2006, the American Association of University Women found that 62% of female and 61% of male college students had experience being sexually harassed at their university. In Japan, sexual harassment of students by teachers is so prevalent it has been given its own acronym--SHOC, for "Sexual Harassment on Campus”. A research in Japan by the Women’s Studies Education Network showed that about 15% of undergraduates, about 34% of graduate students, and about 36% of the teaching staff (both full-time and part-time) had experienced some forms of sexual harassment (Takashi, 2001). This paper presents a discussion about the understanding of employees in institutions of higher learning about the issue of sexual harassment. Understanding and being aware about sexual harassment help staff of universities to seek appropriate intervention when they are faced with sexual harassment issues. The study on which this paper is based briefly surveys the understanding about sexual harassment amongst staff members in two universities in Malaysia. A total of 224 male and female staffs of Universiti Sains Malaysia (USM) and Universiti Malaysia Sabah (UMS) answered a short survey given to them at the beginning of training programmes on sexual harassment. The results show that staffs have a relatively high understanding about incidents of sexual harassment. The research indicates that there is a substantial number of incidents of sexual harassment on campuses and victims of sexual harassment tend to be female. Staff’s experiences of sexual harassment also correlate with their understanding and awareness of sexual harassment.